Certainty Equivalent in Capital Markets - Lutz Kruschwitz; Andreas Löffler (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2003)
We generalize the classical concept of a certainty equivalent to a model where an investor can trade on a capital market with several future trading dates. We show that if a riskless asset is traded and the investor has a CARA utility then our generalized certainty equivalent can be evaluated using the sum of discounted one-period certainty equivalents. This is not true if the investor has a HARA utility.
Keywords: D81; D92; 330; certainty equivalent; CARA; Erwartungsnutzen; Kapitalmarkttheorie; Risikoaversion; Nutzenfunktion; Theorie; Entscheidung bei Unsicherheit